Hate crimes hurt more: Can restorative practices help repair the harms? - Walters, M (2012)
The current retributive approach to tackling hate crime, while intuitively grounded in the principle of proportionately, does little to either repair the harms caused by incidents of hate or engender greater levels of acceptance of those deemed as “different”. This thesis therefore explores whether restorative justice, a relatively new theory and practice of criminal justice, is better placed to tackle the causes and consequences of hate victimisation. The 18 month empirical study, carried out to examine the thesis’ aims, uses a triangulation approach by incorporating observations of restorative justice meetings, semi-structured interviews with victim participants and semi-structured interviews with restorative practitioners who have experience facilitating hate crime cases. The mainly qualitative data collated provides for a detailed evaluation of the various processes found within restorative practices that: 1) helped to alleviate the distress caused by hate victimisation and 2) prevented the recurrence of hate-motivated incidents. A broad conceptualisation of hate crime was used within the thesis that included “hate incidents”. This allowed me to explore the utility of restorative practices in cases involving serious violence and the more pervasive “low-level”, but nonetheless highly deleterious, non-criminal incidents of hate that are frequently committed against minority group individuals. There were also several unanticipated findings from the study. First, data emerged which highlighted various aspects of the restorative practice which were unforeseen as being central to the successful application of restorative processes, these are discussed throughout the thesis. Second, great insight was gained into the nature of hate victimisation, helping to unravel some of the complex socio-cultural factors pivotal to both the cause and effect of hate victimisation. It is hoped that these additional findings provide important epistemological advancements in both fields of study.